Charitable endowment (waqf) for the benefit of parentless children in Malaysia: a preliminary study - Mohd, Azizah; Ibrahim, Badruddin; Baharudin, Mohammad Hidir (IIUM Press, International Islamic University Malaysia, 2018)
Children are part of the world population and the future of a Nation. Being weak and vulnerable subjects, children deserve full protection from all angles. Adequate protection of children population may guarantee potential and quality leaders for the global world in future. In Malaysia, children form part of the whole Malaysian population. Many children are parentless and having no guardian. These children are in need of protection in all forms. It is obvious that one of the means to protect parentless children is by safeguarding their welfare and benefit through charitable endowment (waqf) provision. This paper seeks primarily to examine charitable endowment (waqf) as a means of safeguarding parentless children's welfare and benefit. The examination focuses on the theoretical framework of Islamic law relating to waqf in Malaysia as well as the concept and scope of parentless children. The research is basically library research as it is a preliminary stage to provide a sound framework for a further study on the instrument of waqf as administered by States Islamic Religious Council for parentless children's benefit in Malaysia. It is believed that the finding of this research will provide a further avenue for future research on the administration of waqf for the benefit of parentless children in Malaysia.